Changes in post-treatment cardiac PET avidity predict overall survival in lung cancer patients treated with chemoradiation: Secondary analysis of the ACRIN 6668/RTOG 0235 clinical trial. (June 2022) - Miller, Ryan; Santangelo, Tess; Forghani-Arani, Farnoush; Rusthoven, Chad; Chen, Yingxuan; Castillo, Edward; Castillo, Richard; Guerrero, Thomas; Vinogradskiy, Yevgeniy
Highlights: The authors of this manuscript have no other conflicts of interest to report. FDG-PET changes in the heart for lung cancer patients can predict clinical outcomes. Median overall survival for patients with a negative SUVmean cardiac change was 413 days. Median overall survival for patients with a positive SUVmean cardiac change was 585 days. Abstract: The purpose of this work was to use data from a large co-operative group trial to evaluate whether metabolic FDG-PET changes in the heart for lung cancer patients can predict for clinical outcomes. The study found that cardiac SUV changes following definitive chemoradiation are significantly (HR 0.811, 95% CI 0.68–0.96, p  = 0.017) associated with overall survival in locally advanced NSCLC patients. If validated in a prospective cohort, our data show the potential for cardiac metabolic changes to be an early predictor for clinical outcomes.